P-105 A UNIQUE AND MULTIDISCIPLINARY APPROACH TO ABDOMINAL DEFECT CORRECTION AFTER TRAM FLAP. (13th October 2022) - Fonseca, T; Andrade Almeida, M; Campos, E; Barbosa, E; Barbosa, E
Abstract: Aim: The Transverse Rectus Myocutaneous (TRAM) flap is a valid option in autologous breast reconstruction with acceptable aesthetic results, but the absence of the rectus muscle can be responsible for the discomfort and functional lost caused be the asymmetry of the abdominal wall with a slight bulge. It's also described that incisional hernias can develop following TRAM, and the management is often challenging. We want to present a case of a multidisciplinary surgery with immediate correction of the abdominal defect after the TRAM flap. Material and Methods: We describe a case of a woman who, at the same surgical time, underwent skin-sparing mastectomy with immediate reconstruction with a TRAM flap and correction of the muscle defect of the abdominal wall with transverse abdominis release (TAR) with placement of a wide, macroporous polypropylene mesh with 48mg/m2 density in a retromuscular position. Results: The association of the TAR with the placement of a wide mesh retromuscular allows a greater containment of intraabdominal force, with less bulging and better aesthetic results at the muscle donor site. Conclusion: The correction of the muscle defect should be considered at the same time of the TRAM flap. The multidisciplinary approach in these cases can reduce the patient's surgical morbidity and allow better aesthetic and functional outcomes. Note: we use a DIPROMED®, BULEVB5050 mesh